Local anesthetic methods used by UK NHS general dental practitioner's for mandibular central incisor anesthesia: A study - Aesa Alzaroug Jaber; Karthikeyan Ramalingam; Whitworth John Martin; Corbett Ian; Meechan John (Wolters Kluwer Medknow Publications, 2015)
Objective: To determine the methods of dental local anesthesia employed by UK general dental practice to anesthetize mandibular central incisor teeth and to evaluate any variations with the technique with an increase in experience. Materials and Methods: A total of 233 general dental practitioners attending postgraduate courses in dental local anesthesia and British Endodontic Society meeting completed a written questionnaire. Respondents were requested to provide information on their year and university of qualification, their location of practice and the primary local anesthetic technique employed for pulp extirpation of an inflamed vital mandibular permanent incisor. Analysis was undertaken to determine whether dentists qualified for <5 years, between 5 and 10 years and >10 years adopted different strategies. Data were analyzed by Chi-square test. Results: Buccal infiltration was employed by 110 (49.1%) practitioners. There were significant differences in choice of anesthetic method among practitioners of differing seniority. Conclusions: Buccal infiltration is the most commonly used the local anesthetic method to anesthetize the permanent mandibular central incisor teeth. More experienced practitioners, qualified >10 years, were more likely to employ a combination of methods from the outset.